Ontogeny of adventitious shoots of Citrus sinensis (Linn.) Osbeck cv. pêra cultivated in vitro according to the type of explant used - Simões, Maria Olivia M.; Silva, Eldo A. M.; Teixeira, Silvio L. (Pesquisa Agropecuaria Brasileira, 1991)
Five regions were isolated from Citrus sinensis (Linn) Osbeck cv. Pêra branch internode segments and cultivated in vitro, to study the origin and development of callus and stem primordium. The isolated explants were: a) "complete internode"; b) "epidermal layer (epidermis and a few cortical cells); c) "bark" (epidermis, cortex, phloem and external cambial zone layers); d) "central cylinder" (internal cambial layers, xylem and pith); and e) "rejoining" (rejoining of bark with central cylinder). "Complete internode", "bark" and "rejoining" initiated callus formation from the cambial zone. In the "epidermal layer" and "central cylinder" the callus development occurred by the reversal of differentiation of mature tissues, respectively from the cortical cells and xylem ray cells. Cytological observations showed much starch storage before primordium formation in the callus. "Bark" was the region that showed lesser contamination, faster callus formation and a greater number of primordia and shoots than the other isolated regions.